2017
DOI: 10.1177/0263617417704527
|View full text |Cite
|
Sign up to set email alerts
|

Surface characteristics of KOH-treated commercial carbons applied for CO2 adsorption

Abstract: The effect of an alkali treatment (potassium hydroxide) on the properties of a commercial activated carbon has been studied. The aim of the treatment was to improve the adsorption properties of the material toward carbon dioxide. In the result of the treatment, silica contained in the raw carbon was removed and the density of the material increased. The changes in the surface chemistry were observed as well. The treatment of the activated carbon with KOH resulted in a complete removal of carboxy and lactone gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…It is generally known that with an increase in temperature, there is a transition from physisorption to chemisorption. In one of our previous papers [48], we described CO 2 adsorption studies on commercial activated carbon (pure and modified with KOH) using temperature-programmed desorption method (TPD-CO 2 ) performed under atmospheric pressure at three different temperatures: −30, 0, and 20 • C. Significant changes in adsorption energy were observed with increasing temperature, corresponding to the growing contribution of chemisorption to physisorption. We concluded that at higher temperatures, the adsorption of carbon dioxide on activated carbon had a mixed (physical/chemical) character and that two types of adsorption sites are present at the surface.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally known that with an increase in temperature, there is a transition from physisorption to chemisorption. In one of our previous papers [48], we described CO 2 adsorption studies on commercial activated carbon (pure and modified with KOH) using temperature-programmed desorption method (TPD-CO 2 ) performed under atmospheric pressure at three different temperatures: −30, 0, and 20 • C. Significant changes in adsorption energy were observed with increasing temperature, corresponding to the growing contribution of chemisorption to physisorption. We concluded that at higher temperatures, the adsorption of carbon dioxide on activated carbon had a mixed (physical/chemical) character and that two types of adsorption sites are present at the surface.…”
Section: Resultsmentioning
confidence: 99%
“…23 The peaks in the range of 2700-3000 cm À1 can be attributed to the C-H bending vibration. 24 Two peaks at 2870 and 2930 cm À1 , associated with the anti-symmetric and symmetric stretching vibration of CH 2 from HDTMA chain. 25 The band in the region 1600-1750 cm À1 can be assigned to C]O group.…”
Section: Morphology and Interfacial Characterizationmentioning
confidence: 99%
“…27,28 The broad peaks in the range of 500-750 cm À1 correspond to CH 2 rocking (719 cm À1 ) 29 and C-O stretching. 24 The band at 488 cm À1 can be attributed to the anti-symmetric bending mode of the quaternary (alkyl) mode of the head of the methyl group (CH 3 ) 3 N + in HDTMA. 25,30 The contact angle measurement revealed the wetting behavior, the change of hydrophobic and hydrophilic intensity of both AC and AC-S.…”
Section: Morphology and Interfacial Characterizationmentioning
confidence: 99%
“…10 Bandi et al 11 investigated the absorption of CO 2 by adding KOH inside a packed column with a total height of 2 m. It was concluded that the CO 2 absorption from ambient air was around 70%. Lendzion-Bielu n et al 12 investigated the effect of KOH treatment on the surface properties of activated commercial carbon to improve the adsorption capacity of CO 2 . They reported an increase in the concentration of hydroxyl groups on the surface, which led to an increase in the uptake value of CO 2 by 14% at 0 C. In another study performed by Keith et al, 13 aqueous KOH solution was combined with calcium caustic recovery loop to capture about 1Mt-CO 2 /year from ambient air in an industrial plant.…”
Section: Introductionmentioning
confidence: 99%